GUI for ionospheric research - Norehan Binti Zahidi (2023)
This is a software development based project. This project is about a development of Graphical User Interface (GUI) by using MATLAB. It requires author to build a graphical user interface (GUI) platform for the ionospheric study and use own creativity to design, link and display results in a user-friendly manner. The main target is to develop GUI for ionospheric research and to ensure that the platform of capability is in the easiest way especially to link and display the result such as the ionogram, values for height of F-layer, foF2, fxF2 and critical frequency of foF2 and fxF2 without any error.